The Graph Rewriting and Transformation Language: GReAT - Balasubramanian, Daniel; Narayanan, Anantha; van Buskirk, Christopher; Karsai, Gabor (Electronic Communications of the EASST, 2007)
In this paper, we describe the language and features of our graph transformation tool, GReAT.We begin with a brief introduction and motivation, followed by an overview of the actual language, the modeling framework, and the tools that were written to support transformations. Finally, we compare GReAT to other similar tools, discuss additional functionality we are currently implementing, and describe some of our experiences with the tool thus far.